Defects-engineered tailoring of tri-doped interlinked metal-free bifunctional catalyst with lower gibbs free energy of OER/HER intermediates for overall water splitting. (March 2022) - Yasin, G.; Ibraheem, S.; Ali, S.; Arif, M.; Ibrahim, S.; Iqbal, R.; Kumar, A.; Tabish, M.; Mushtaq, M.A.; Saad, A.; Xu, H.; Zhao, W.
Abstract: Controllable tailoring of metal-free/carbon-based nanostructures tends an encouraging way to enhance the bifunctional activity of electrodes, but a great challenge owing to the sluggish kinetics of oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). Herein, a facile tempted-defects assisted fractionation strategy is presented to synthesize N, S, and O tri-doped metal-free catalyst (DE-TDAP). Due to this effective tempted-defects and heteroatoms interlinking in DE-TDAP, it delivers the lowest overpotential toward both the OER (346 mV) and HER (154 mV) at 10 mA cm −2 . Remarkably, the DE-TDAP-electrode carries only a cell voltage of 1.81 V at 10 mA cm −2 for overall water splitting and long-term stability. Considerably, the density functional theory (DFT) calculation exposes that the tailored-defects in tri-doped interlinking could enhance bifunctional catalytic performance devising from lower Gibbs free energy of OER/HER intermediates on active sites. This struggle henceforth provides a perceptive understanding of the synergetic principles of heteroatom-interlinking-tailoring nanostructures in water splitting. Graphical abstract: Image 1 Highlights: We succeeded in constructing the cost-efficient and metal-free defective tri-doped-asphaltene (DE-TDAP). The engineered defects of interlinked heteroatom-doped material are advantageous for electrocatalysis. The metal-free catalyst shows outstanding catalytic performance toward OER (η10 = 346 mV) and HER (η10 = 154 mV). Water electrolyzer prepared with metal-free electrode validates only a cell voltage of 1.81 V at 10 mA cm −2 . DFT calculations unveil the origin of higher OER/HER performance via defects engineering of interlinked heteroatoms doping.